On the convergence of Kurchatov-type methods using recurrent functions for solving equations - I. K. Argyros; S. Shakhno; H. Yarmola (Математичні Студії, 2022)
We study a local and semi-local convergence of Kurchatov's method and its two-step modification for solving nonlinear equations under the classical Lipschitz conditions for the first-order divided differences. To develop a convergence analysis we use the approach of restricted convergence regions in a combination to our technique of recurrent functions. The semi-local convergence is based on the majorizing scalar sequences. Also, the results of the numerical experiment are given.